2018
DOI: 10.1159/000495239
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA SNHG16 Promotes Cell Proliferation by Sponging MicroRNA-205 and Upregulating ZEB1 Expression in Osteosarcoma

Abstract: Background/Aims: Long noncoding RNAs (lncRNAs) have been a research hotspot, as they play important roles in tumor development. However, their expression pattern and biological function in osteosarcoma have not yet been clarified. Methods: Differentially expressed lncRNAs in osteosarcoma and paracarcinoma tissues were identified by screening an lncRNA microarray, and candidate lncRNAs were verified by quantitative real-time PCR (qRT-PCR). A series of bioinformatics and molecular biological methods were adopted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 21 publications
(31 reference statements)
1
40
1
Order By: Relevance
“…For example, SNHG16 facilitates cell proliferation via activating WNT signaling pathway in esophageal squamous cell carcinoma (ESCC) (Han et al, 2018). SNHG16 upregulates ZEB1 expression to drive osteosarcoma cell proliferation via sponging miRNA‐205 (Zhu et al, 2018). In addition, a previous study has revealed that SNHG16 as a ceRNA facilitates lipopolysaccharides‐induced acute pneumonia through miR‐370‐3p/IGF2 axis (Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For example, SNHG16 facilitates cell proliferation via activating WNT signaling pathway in esophageal squamous cell carcinoma (ESCC) (Han et al, 2018). SNHG16 upregulates ZEB1 expression to drive osteosarcoma cell proliferation via sponging miRNA‐205 (Zhu et al, 2018). In addition, a previous study has revealed that SNHG16 as a ceRNA facilitates lipopolysaccharides‐induced acute pneumonia through miR‐370‐3p/IGF2 axis (Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…30 SNHG16 was also overexpressed in human osteosarcoma tissues and cell lines when compared to matched normal tissues and cell lines, respectively. 16,[36][37][38][39] Osteosarcoma patients with high SNHG16 expression are more likely to have shorter survival, larger tumors, more advanced TNM stage, metastasis, and poorer prognosis. 37,39 Zhou et al revealed that high expression of SNHG16 was associated with poor clinical pathological parameters and shorter OS and progression-free survival, which indicated that it can act as an independent prognostic factor of glioma.…”
Section: Overexpression Of Snhg16 and Clinical Significance In Cancermentioning
confidence: 99%
“…However, in osteosarcoma, mechanistic investigations revealed that SNHG16 could act as a sponge for miR-98-5p, miR-1301, miR-16, miR-340, and miR-205. 16,[36][37][38][39] Inhibition of miR-98-5p and miR205 increases zinc finger E-box binding homeobox 1 (ZEB1), E2F transcription factor 5 (E2F5), and STAT3 expression to promote tumorigenesis. 36,37 Li et al reported that SNHG16 was revealed to bind with miR-200a-3p, leading to the proliferation of CRC cells.…”
Section: Implication Of Snhg16 In the Hallmarks Of Cancer Promoting Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers showed that lnc RNA could alter gene expression by modifying the effects of other non-coding RNA, such as miRNA [4]. Studies suggest that lncRNA modulates miRNA function by acting as a sponge to absorb the miRNA and prevent it from degrading its mRNA target [5,6]. Alternatively, lncRNA may antagonize the actions of miRNA by competing with them for binding to their mRNA targets [7].…”
mentioning
confidence: 99%